Prevalence of overt postpartum urinary retention and its risk factors: study in a tertiary care center, Jumla - Mainali, Deepa; Bhandari, Jeetendra; Pradhan, Anuradha; Tamrakar, Prashamsha; Mahat, Pradeep; Gautam, Sundar (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Postpartum urinary retention (PUR) is the inability to void voluntarily after delivery, with overt PUR defined as no spontaneous voiding within six hours post-vaginal delivery or requiring re-catheterization post-cesarean. In rural Nepal, PUR risks bladder overdistension, detrusor failure, and renal complications due to limited monitoring. This study assessed the prevalence of overt PUR and risk factors, including primigravida status, gestational age, neonatal birth weight, delivery mode, perineal tears, episiotomy, vulvar edema, and prepartum catheterization.Methods: This was a Prospective cross-sectional study conducted at Karnali Academy of Health Sciences, Jumla, from November 2022 to July 2023 among postpartum females. Data were collected using a pre-formatted pro forma after obtaining informed consent. Sampling was conducted using a convenience sampling technique, with a sample size of 78 (expected prevalence: 5.37%; 95% CI; 5% margin of error). Analysis was done in Microsoft Excel and SPSS v16.0. Chi-square, Fisher’s exact, and Mann-Whitney U tests were applied based on the data distribution.Results: Overt PUR prevalence was 3 (3.8%). Primigravida was significantly associated (p=0.027). No significant associations were observed with age (median 24 years), gestational age (91% at term, p=0.750), neonatal weight (median 3000 grams, p=0.471), delivery mode (67% vaginal, p=0.547), perineal tears (first degree, p=0.99, second degree, p=0.280), episiotomy (p=0.216), vulvar edema (p=0.99), or catheterization (p=0.547).Conclusion: Primigravida elevates overt PUR risk in rural settings; recommend targeted postpartum screening for primipara to prevent complications.